2020
DOI: 10.1007/s11657-020-0693-z
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Framework of Fracture Liaison Services in Spain and their coordination with Primary Care

Abstract: The coordination of Fracture Liaison Services (FLS) with Primary Care (PC) is necessary for the continuity of care of patients with fragility fractures. This study proposes a Best Practice Framework (BPF) and performance indicators for the implementation and follow-up of FLS-PC coordination in clinical practice in Spain. Purpose To develop a BPF for the coordination of FLS with PC in Spain and to improve the continuity of care for patients with fragility fractures. Methods A Steering Committee selected experts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
1
3
0
4
Order By: Relevance
“…This is the first study to report on the incidence rate of imminent fractures after an osteoporotic sentinel fracture in Spain, with age, sex, and skeletal location of the index fractures as possible risk factors. Our results support the increased risk of imminent fracture after a recent fracture and provide key elements for early identification of risk and the application of targeted strategies aimed at preventing future fractures and mortality, such as the interventions recommended by the Fracture Liaison Services [ 36 ].…”
Section: Discussionsupporting
confidence: 67%
“…This is the first study to report on the incidence rate of imminent fractures after an osteoporotic sentinel fracture in Spain, with age, sex, and skeletal location of the index fractures as possible risk factors. Our results support the increased risk of imminent fracture after a recent fracture and provide key elements for early identification of risk and the application of targeted strategies aimed at preventing future fractures and mortality, such as the interventions recommended by the Fracture Liaison Services [ 36 ].…”
Section: Discussionsupporting
confidence: 67%
“…Finally, we found that communication between FLS units and primary care was not as fluid as it should be. Full coordination with primary care is essential to ensure the continuity of care which would improve secondary prevention of fragility fractures [ 38 ], and this should be considered to improve FLS units.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many referral services for the prevention of recurrence fractures are increasing in the world due to good results. Naranjo et al 20 propose the establishment of a framework of good practices and performance indicators to implement and monitor the coordination of fracture services and primary care in clinical practice, demonstrating the need for treatment of secondary fractures. The occurrence of previous fractures and risk factors for osteoporosis are already indicative of the need for specialized follow-up and appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%